Inês de Castro em dois cordéis brasileiros para crianças: uma proposta de manual pedagógico de mediação de leitura pela aplicação do método leratos - Araújo, Juliana do Nascimento (2025)
This research arises from an investigation related to the absence of a strand of Inesian literature for children/youth audiences in the cordel format, mixing popular traditions with historical narratives. The general objective was to analyze and think about ways of reading the tragic story of Inês de Castro adapted for children based on the appreciation of a corpus of Inês de Castro literature aimed at this audience in the form of a dramaturgical cordel, focusing on works by Brazilian authors, selecting two works for this purpose: The story of Inês de Castro or the blonde lady who, after her death, became queen (Sombra, 2011) and Almas livre (Almeida, 2022). As specific objectives we indicate the following: a) Investigate and draw an analytical panorama of Ines's literary fortune in the cordel format adapted for children in Brazil; b) Analyze the representations of the myth of Inês de Castro in the two works that make up the corpus of Inês de Castro literature in comparison with the more general historical accounts about the character; c) Carry out a comparative, intermedia and intercultural study of the works based on different indicators that characterize the literary genre and d) Develop a Pedagogical Manual based on the LerAtos Method, proposing a reading mediation experience to be carried out by elementary school teachers, so that the myth of Inês de Castro can be taken as the basis for a process of early awareness and awareness about violence against women and, in general, about gender inequalities. This study also brings together pertinent discussions about the history, legend and myth of the post-mortem queen of Portugal in the 14th century, D. Inês de Castro, and her symbolic and cultural legacy until the present century, based on references such as Gil (1975), Sousa (1987), Osakabe (1998), Aristóteles (2011), Jacoto (2008), Toledo (2008), Rocha (1996), Almeida, Andrade and Barros (2021). The dissertation also includes discussions about the analysis of the dramaturgical strings that make up the literary corpus based on the theoretical postulations of Rosenfeld (1985), Prado (1970), Hutcheon (2013), Reis (2017) and Coccia (2020); notes related to historical and contemporary perspectives linked to the concepts of childhood with the concepts of Ariès (1981 and 1986), Postman (1999) and Coelho (2011); perspectives focused on the literary reading of Inesian themes as a strategy for preventing violence against women, specifically feminicide as an outcome of Andrade’s studies (2021); and finally, a proposal for a law authored by the myth of Inês de Castro by applying the LerAtos method in the classroom, with the aim of training readers who are passionate about reading, and not just sensitized, from childhood, to issues of gender, prejudice and violence. To do so, we used the concepts of McGonigal (2012) and Barros and Andrade (2017).